Analisis Abnormal Return Saham, Likuiditas Saham, dan Volume Perdagangan Saham Sebelum dan Sesudah Pemecahan Saham (Stock Split)(Pada Perusahaan Go Publik yang Terdaftar di Bursa Efek Indonesia Periode 2011-2015) - Amelia, Lia, Drs. Agus Endro Suwarno, M.Si (2017)
This study aims to determine and analyze the extent to which the stock split event can influence the public or the owners of the funds (investors) in trading stocks with a variable measuring the difference in abnormal returns, liquidity and trading volume of the stock before and after the stock split at a go public company listed on the Stock Exchange Office Indonesia period 2011-2015. The data used in research were taken from secondary data in terms of announcement date of stock split applied as event date ( t_0 ), daily closing price, indeks daily closing of the companies applying stock split within observation period ( IHSG ), the amount of daily traded share and the amount of listed share.The sampling method used is purposive sampling number of samples based on predetermined criteria is 35 samples companies which implemented stock split.The analytical method used is the test for normality of data using one sample kolmogorov smirnov test and hypothesis testing used different test analysis model (Paired Sample T-test).Based on the result of hypotheses testing, the first hypothesis states that there are no differences in abnormal return before and after the stock split. While the second and third hypothesis shows that there are differences in the liquidity and stock trading volume of shares before and after stock split.